We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
437
2
avatar+21 

 

 Dec 13, 2017
 #1
avatar+104712 
+2

Mmmmmm...... looks lke the first step is incorrect.....

 

2x  -  4y  =  -6

3x  +  2y  = -1

 

6x - 12y  =  -18                ⇒  Multiplication Property of Equality

-6x - 4y  =     2

 

-16y  =  -16                    ⇒   Addition Property of Equality  (with simplification )

 

y  =  1                            ⇒  Division Property of Equality

 

2x  -  4(1)  =  - 6            ⇒  Substitution  

 

2x  -  4    =  - 6                ⇒  Simplification of previous step

 

2x    =   - 2                     ⇒  Addition Property of Equality

 

x  =  -1                            ⇒  Division Property of Equality

 

 

cool cool cool

 Dec 13, 2017
 #2
avatar+21 
+1

Thank You!!!

NewuserEthan  Dec 13, 2017

20 Online Users

avatar